2016
DOI: 10.1007/s13181-016-0566-4
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin B12 Analog Cobinamide Is an Effective Antidote for Oral Cyanide Poisoning

Abstract: Introduction Cyanide is a major chemical threat, and cyanide ingestion carries a higher risk for a supra-lethal dose exposure compared to inhalation but provides an opportunity for effective treatment due to a longer treatment window and a gastrointestinal cyanide reservoir that could be neutralized prior to systemic absorption. We hypothesized that orally administered cobinamide may function as a high-binding affinity scavenger and that gastric alkalinization would reduce cyanide absorption and concurrently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Oral cyanide has also been used in rabbits for the assessment of cobinamide efficacy . Similar to the current experiment, sodium cyanide was used as the challenge agent, though it was given via feeding tube to anaesthetized rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral cyanide has also been used in rabbits for the assessment of cobinamide efficacy . Similar to the current experiment, sodium cyanide was used as the challenge agent, though it was given via feeding tube to anaesthetized rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Both the dinitrocobinamide and aquohydroxocobinamide were then also given via gastric tube, with the rationale that a treatment that could be given IM as well as orally would improve the antidote's usefulness in a mass‐casualty scenario. The authors found that a single dose of dinitrocobinamide or aquohydroxocobinamide co‐administered with bicarbonate increased survival from 0% to 50% and 67%, respectively …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High Dose Cyanide (50 mg NaCN) with Simultaneous Oral Therapy Six of the 10 animals in Group 6 were previously used as controls and reported in a prior study of oral cobinamide treatment [17].…”
Section: Study Design and Treatment Groupsmentioning
confidence: 99%
“…At a pH above 10.3, >90% of ingested cyanide would be in the ionized form. We recently showed we could rescue rabbits from a lethal dose of oral cyanide using the combination of oral cobinamide and sodium carbonate [17]. However, cobinamide is relatively expensive, is absorbed from the GI tract and has some toxicity when administered parenterally at high doses, and is not FDA approved.…”
Section: Introductionmentioning
confidence: 99%